A right angle triangle A B C is such that A C = 2 4 cm, C B = 1 0 cm and ∠ A C B = 9 0 ∘ . A point D on C B is such that when point C is reflected upon line A D , the reflected point will be on line A B . The length of C D = b a where a and b are coprime integers. Find the value of a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Reflection means we have to draw a perpendicular from point 'c' to line AD (mark it as E) and then to extend it till AB (mark it as F), then CE=EF, hou u can draw C'D in your figure,
Log in to reply
Ya you can do that and you'd realise that F = C ′ . I can draw C ′ D , it is the reflection of C D .
Did the problem in the very same manner!!
same way , i hate similarities
I addressed the problem in the same way you did in the beginning, but then i found CD in a different way. Instead of considering the areas of the triangles like you did, i just concentrated on the little triangle C'BD. With Pythagoras' Theorem we'll have: C'D²+C'B²=BD² And since: C'D=CD , C'B=AB-AC'=26-24=2 and BD=CB-CD=10-CD Then: C'D²+C'B²=BD² => CD²+2²=(10-CD)² => CD²+4=100-20CD+CD² => CD=96/20=24/5
If P is the symmetric of C from A D then Δ A C D = Δ A P D .
Then A D is a bisector. Then by using the bisector theorem we have.
C D D B = A C A B .
By adding 1 to the proportion we get
C D B C = A C A C + A B .
Which will give us the result.
Easy question Solve the question just like you
Problem Loading...
Note Loading...
Set Loading...
Firstly by Pythagoras Theorem, A B = 2 4 2 + 1 0 2 = 2 6
Now let C ′ be the relfected point of C by line A D .
Considering the area of triangles; (let [ A B C ] denote the area of triangle A B C )
[ A B C ] = [ A C D ] + [ A D B ]
⇒ 2 1 ( 2 4 ) ( 1 0 ) = 2 1 ( 2 4 ) ( C D ) + 2 1 ( 2 6 ) ( C ′ D )
⇒ 2 1 ( 2 4 ) ( 1 0 ) = 2 1 ( 2 4 ) ( C D ) + 2 1 ( 2 6 ) ( C D )
⇒ ( 2 4 ) ( 1 0 ) = ( 2 4 ) ( C D ) + ( 2 6 ) ( C D )
⇒ 5 0 C D = 2 4 0
⇒ C D = 5 2 4
Hence a + b = 2 4 + 5 = 2 9